Aerodynamic forces on generic buildings subject to transient, downburst-type winds. Issue 137 (February 2015) - Jesson, Michael; Sterling, Mark; Letchford, Chris; Haines, Matthew
Abstract: Having been identified as the cause of design load winds in many parts of the world, transient winds such as gust fronts and thunderstorm downbursts have been increasingly researched over recent years. The difficulties in simulating the flow structure of downbursts in the laboratory, particularly their rapid radial acceleration and associated ring vortices, have complicated measuring wind loads on structures subject to these conditions. The University of Birmingham Transient Wind Simulator (UoB-TWS, a 1 m diameter impinging jet with aperture control) has been used to simulate the transient aspects of downburst-like flow, allowing the pressure distributions they create over cube and portal framed structures to be measured for the first time, at model-scale (1:1600). Analysis of the velocity and pressure fields show that the simulator is capable of creating velocity fields which are similar to those observed in nature. Development of the ring vortex is demonstrated through phase-plot analysis. Two methods of calculating the turbulence intensity of the unsteady flow field have been used, giving mean values of between 3% and 10% depending on the method. Force coefficient time series have been estimated with the buildings angled at 0°, 45° and 90° to the radial wind direction. These are presented along with the instantaneous pressure coefficient distribution at the time of maximum roof suction. This novel research also highlights the difficulties of undertaking transient flow at model scale and drawing conclusions which are applicable to full-scale, i.e., where no two events are the same.